The concrete Diplodocus of Vernal—a cultural icon of Utah (Geology of the Intermountain West, 2023)
Although many casts have been made of the Carnegie Museum’s iconic Diplodocus, initially in plaster and more recently in various plastics, one stands alone as having been cast in concrete. This skeleton, made from the original Carnegie molds starting in 1956–1957, was unveiled at the Utah Field House of Natural History in Vernal, Utah, in 1957, and stood outside the museum for three decades. The fate of the molds after this casting is uncertain. The concrete Diplodocus was the museum’s icon for 32 years until the weather damage became too great. The cast was then taken down and repaired, and fresh molds made from it by Dinolab in Salt Lake City. From these molds, a new replica was cast in water-expanded polyester and mounted inside the Field House. This cast was moved to the Field House’s new location in 2004 and was remounted in the atrium, but the old concrete cast could not be easily remounted and was instead transferred to the Prehistoric Museum at Price, Utah. It has, however, yet to be remounted there, as it awaits a new building for the museum. Meanwhile, the new molds have been used to create more Diplodocus casts that are mounted in Japan and elsewhere, and have also furnished missing parts of the iconic rearing Barosaurus skeleton in the atrium of the American Museum of Natural History in New York City. Thus, the concrete Diplodocus of Vernal has become one of the most influential of all Diplodocus specimens, second only to the Carnegie original.